PENINGKATAN AKTIVITAS DAN HASIL BELAJAR TOUR PLANNING DAN TOUR GUIDING MELALUI METODE OUTDOOR STUDY BAGI GURU/PESERTA DIKLAT USAHA PERJALANAN WISATA (Study Kasus di Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Bisnis dan Pariwisata) - Etty Sulistyawati; Dayat Hidayat; Sarwani . (Inovasi, 2014)
Improvement Activity and Results Study Tour Planning and Tour Guiding Through Outdoors Study Method For Teachers / Business Travel Workshop Participants (Case Study at the Center for Development and Empowerment of Teachers and Education Personnel Business and Tourism). The purpose of this training action research is to increase the activity and learning outcomes of the material planning and tour guiding tour through outdoor learning method study on business training tour advanced level. This study was conducted using action research design (Action Research). This means that training is conducted action research because it provides an orderly framework for solving practical problems. Action research training are also empirical because it relies on real observations and behavioral data. Research training actions diagnose a problem in a particular context and attempt to solve the problem in the context. The research data collection techniques using test techniques, observation, interviews and discussions. Application of outdoor study method can increase the activity of the business training participants tour which reached 84.84% after the implementation of learning in the second cycle than ever before in the first cycle, namely: 59% and the initial conditions: 29%. As for the learning outcomes of the training that the initial conditions 62, in the first cycle at 73 and the second cycle to an average of 86.75. Learning with the application of outdoor study methods together can increase the activity and learning outcomes of the training in the first cycle and cycle II, proved the increasing percentage of study participants of the training activities in line with the average level of learning outcomes. With the methods of outdoor learning training eye study tour planning and tour guiding becomes more enjoyable.